2020
DOI: 10.3390/s20061668
|View full text |Cite
|
Sign up to set email alerts
|

Towards Safety Improvement of Measurement and Control Signals Transmission in Marine Environment

Abstract: This paper is dedicated to some aspects of maritime on-board safety improvement. The contribution of this article is a proposal to extend wireless communication on the ship, supported by examples of solutions that have not previously been used on board. Analyzed aspects concern the measurement and control signal transmission in hostile marine environment. A problem to solve is formulated, how to reduce a negative impact of this environment on effectiveness and reliability of maritime on board communication. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The studies in [16,17] dealt with radio signal propagation measurements inside large ships, exploring both sub-1 GHz and 2.4 GHz bands. Another notable case study in [13] employed Zigbee and WiFi networks, strategically placing routers/repeaters to act as wireless connectors across steel bulkheads. Moreover, Saafi et al [25] proposed the use of 6G solutions for sustainable maritime networks, emphasizing the challenges posed by steel bulkheads.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies in [16,17] dealt with radio signal propagation measurements inside large ships, exploring both sub-1 GHz and 2.4 GHz bands. Another notable case study in [13] employed Zigbee and WiFi networks, strategically placing routers/repeaters to act as wireless connectors across steel bulkheads. Moreover, Saafi et al [25] proposed the use of 6G solutions for sustainable maritime networks, emphasizing the challenges posed by steel bulkheads.…”
Section: Related Workmentioning
confidence: 99%
“…This is largely due to the sophisticated wiring systems used during the shipbuilding phase. Ships already have extensive cable connections for measurement, control, monitoring, and signaling, which makes adding more sensors difficult [12,13]. Wireless communication seems like a workable option in these situations, particularly if the target is situated in an inaccessible place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The history of marine safety is marked by numerous modifications and revisions of maritime industry regulations and standards (Baalisampang et al, 2018). This is because safety on the crew and ship equipment played a vital role in avoiding any accidents and protecting the marine ecosystem (Masnicki et al, 2020). Besides, it has been reported that more than 90% of the world's cargo is shipped by merchant ships; thus, the elements of marine safety became a priority in the maritime industry (Al-Shammari & Oh, 2018).…”
Section: Introductionmentioning
confidence: 99%